2015
DOI: 10.5194/acp-15-9381-2015
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of an unknown daytime HONO source on the mixing ratio and budget of HONO, and hydroxyl, hydroperoxyl, and organic peroxy radicals, in the coastal regions of China

Abstract: Abstract. Many field experiments have found high nitrous acid (HONO) mixing ratios in both urban and rural areas during daytime, but these high daytime HONO mixing ratios cannot be explained well by gas-phase production, HONO emissions, and nighttime hydrolysis conversion of nitrogen dioxide (NO 2 ) on aerosols, suggesting that an unknown daytime HONO source (P unknown ) could exist. The formula P unknown ≈ 19.60[NO 2 ] · J (NO 2 ) was obtained using observed data from 13 field experiments across the globe. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 75 publications
5
50
0
Order By: Relevance
“…Similar underestimations were previously simulated in eastern China (Gao et al, 2015;Liao et al, 2015;. The mean NMB and NME of O 3 in MOD1, calculated at −53.97 and 67.00 %, respectively (Table S1 in the Supplement), were comparable to previous China studies (Li et al, 2012;Tang et al, 2015;Zhou et al, 2017), while the mean NMB and NME of O 3 in MOD2 were ameliorated to −45.83 and 63.61 %, respectively. The SO 2 changes were generally captured in the two simulations in terms of MFB and MFE, but with an overestimation and a low R. In addition to emissions, the absence of pathways converting SO 2 to sulfate in the current WRF-Chem model, such as aqueous-phase oxidation of dis- 3 ) by dissolved NO 2 under conditions of high ammonia (NH 3 ) and NO 2 concentrations (X.…”
Section: Chemical Evaluationsupporting
confidence: 75%
“…Similar underestimations were previously simulated in eastern China (Gao et al, 2015;Liao et al, 2015;. The mean NMB and NME of O 3 in MOD1, calculated at −53.97 and 67.00 %, respectively (Table S1 in the Supplement), were comparable to previous China studies (Li et al, 2012;Tang et al, 2015;Zhou et al, 2017), while the mean NMB and NME of O 3 in MOD2 were ameliorated to −45.83 and 63.61 %, respectively. The SO 2 changes were generally captured in the two simulations in terms of MFB and MFE, but with an overestimation and a low R. In addition to emissions, the absence of pathways converting SO 2 to sulfate in the current WRF-Chem model, such as aqueous-phase oxidation of dis- 3 ) by dissolved NO 2 under conditions of high ammonia (NH 3 ) and NO 2 concentrations (X.…”
Section: Chemical Evaluationsupporting
confidence: 75%
“…The turning point of the contour lines would shift to higher NO x reactivity, which means a more NO x -limited regime appears. Tang et al [37] found that the unknown HONO source could also play a role in the ozone production rate, which improves the O 3 simulation in the Jing-Jin-Ji region. However, the HONO concentrations were constraint to measurement in our study.…”
Section: Empirical Kinetic Modeling Approachmentioning
confidence: 98%
“…Currently, the HONO formation processes, especially during daytime, are still not fully understood. Recent ground-based field measurements showed unexpectedly high daytime concentrations of HONO, which could not be solely explained by atmospheric gas-phase reactions (R1-R3) Su et al, 2008a;Sörgel et al, 2011a;Su et al, 2011;Michoud et al, 2014;Czader et al, 2012;Wong et al, 2013;Tang et al, 2015;Oswald et al, 2015, Meusel et al, 2016 …”
Section: Introductionmentioning
confidence: 99%